2009
DOI: 10.1089/ten.tec.2008.0186
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Equine Adipose Tissue–Derived Progenitor Cells Before and After Cryopreservation

Abstract: In horses, stem cell therapies are a promising tool to the treatment of many injuries, which are common consequences of athletic endeavor, resulting in high morbidity and often compromising the performance. In spite of many advantages, the isolation of stem cells similar to human, from equine adipose tissue, occurred only recently. The aim of this study was to isolate equine adipose tissue-derived progenitor cells (eAT-PC), to characterize their proliferative potential, and to study their differentiation capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
8

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 0 publications
2
41
0
8
Order By: Relevance
“…Cells showed the potential for in vitro differentiation into adipocytes as demonstrated by the presence of red granules identified as lipid droplets in the cytoplasm, similar to those already observed in horse adipose tissue-derived stem cell (Mambelli et al 2009) and stem cells differentiated from umbilical cord blood (Koch et al 2007). The amnion-derived stromal cells also had the potential to be differentiated into This study showed that horse amnion represents a valuable source of stromal cells alternative to bone marrow and fat stem cells.…”
Section: Discussionsupporting
confidence: 75%
“…Cells showed the potential for in vitro differentiation into adipocytes as demonstrated by the presence of red granules identified as lipid droplets in the cytoplasm, similar to those already observed in horse adipose tissue-derived stem cell (Mambelli et al 2009) and stem cells differentiated from umbilical cord blood (Koch et al 2007). The amnion-derived stromal cells also had the potential to be differentiated into This study showed that horse amnion represents a valuable source of stromal cells alternative to bone marrow and fat stem cells.…”
Section: Discussionsupporting
confidence: 75%
“…The differentiation media tested (Stem cell Pro ® kit) demonstrated potential to induce adipogenic and osteogenic differentiation of agouti dental pulp stem cells of agoutis. The protocol for media changes followed the criteria previously reported by Mambelli et al (2009). Both the osteogenic and adipogenic differentiations were visualized by morphological changes observed for a phenotype similar to osteoblasts and adipocytes, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported the characterization of AdMSCs in horses, where the most common processes are osteogenic, adipogenic and chondrogenic (tri-lineage) differentiation of progenitor cells (Vidal et al, 2007(Vidal et al, , 2008Kisiday et al, 2008;Mambelli et al, 2009;Colleoni et al, 2009;Toupadakis et al, 2010;Ahern et al, 2011;Schwarz et al, 2011a,b). Only five recent studies have reported the analyses of surface antigens of AdMSCs by flow cytometry (de Mattos Carvalho et al, 2009;Braun et al, 2010;Pascucci et al, 2011;Raabe et al, 2011;Ranera et al, 2011).…”
Section: mentioning
confidence: 99%